Teaching from Home and Emotional Wellbeing During the Covid-19 Pandemic: Perspectives of Digital Native and Digital Immigrant Lecturers in Malaysia - Chan, Josephine Ie Lyn; Lee, Yuen Beng (Journal of Techno-Social, 2022)
The Covid-19 global pandemic has significantly affected the education sector globally. This study explores the Malaysian higher education lecturers’ emotional wellbeing when teaching from home during the Covid-19 pandemic and the differences between the generational cohorts of digital native and digital immigrant lecturers. A qualitative online interview approach was employed on 13 higher education lecturers throughout Malaysia. The study revealed the emotional wellbeing of higher education lecturers was mainly good despite the initial challenges of teaching from home during the pandemic. Stereotypical differences between digital natives and digital immigrants were somewhat evident in the study. Several recommendations were proposed to manage the emotional wellbeing of lecturers while teaching from home.